Influenza passaging annotations: what they tell us and why we should listen. Issue 1 (30th June 2019) - DuPai, Cory D; McWhite, Claire D; Smith, Catherine B; Garten, Rebecca; Maurer-Stroh, Sebastian; Wilke, Claus O
Abstract: Influenza databases now contain over 100, 000 worldwide sequence records for strains influenza A(H3N2) and A(H1N1). Although these data facilitate global research efforts and vaccine development practices, they also represent a stumbling block for researchers because of their confusing and heterogeneous annotation. Unclear passaging annotations are particularly concerning given the recent work highlighting the presence and risk of false adaptation signals introduced by cell passaging of viral isolates. With this in mind, we aim to provide a concise outline of why viruses are passaged, a clear overview of passaging annotation nomenclature currently in use, and suggestions for a standardized nomenclature going forward. Our hope is that this summary will empower researchers and clinicians alike to more easily understand a virus sample's passage history when analyzing influenza sequences.